Re-Exploration for Bleeding or Tamponade after Cardiac Surgery: Impact of Timing and Indication on Outcome - Haneya, Assad; Diez, Claudius; Kolat, Philipp; Suesskind-Schwendi, Marietta von; Ried, Michael; Schmid, Christof; Hirt, Stephan W. (The Thoracic and Cardiovascular Surgeon, 2015)
Objectives Re-exploration after cardiac surgery remains a frequent complication with adverse outcomes. The aim of this study was to evaluate the impact of timing and indication of re-exploration on outcome.Methods A retrospective, observational study on a cohort of 209 patients, who underwent re-exploration after cardiac surgery between January 2005 and December 2011, was performed. The cohort was matched for age, gender, and procedure with patients who were not re-explored during the same period.Results The intraoperative and postoperative transfusion requirements were higher in the re-exploration group (p < 0.01). Patients in the re-exploration group had significantly higher incidences of postoperative acute renal injury (10.0 vs. 3.3%), sternal wound (9.1 vs. 2.4%) and pulmonary (13.4 vs. 4.3%) infections, longer ventilation time (22 [range, 14–52] vs. 12 [range, 9–16] hours) and intensive care unit stay (5 [range, 3–7] vs. 2 [range, 2–4] days), and higher mortality rate (9.6 vs. 3.3%). However, the multivariate logistic regression analysis demonstrated that not the re-exploration itself, but the deleterious effects of re-exploration (blood loss and transfusion requirement) were independent risk factors for mortality. Mortality was 5.3% for patients who were re-explored within the first 12 hours and 20.3% for patients who were re-explored after 12 hours (p = 0.003). Mortality was 3.6% for patients with bleeding and 31.4% for patients with cardiac tamponade for indication of re-exploration (p < 0.001).Conclusions This study suggests that re-exploration after cardiac surgery is associated with increased mortality and morbidity. Patients with delayed re-exploration and suffering from cardiac tamponade have adverse outcome.
Keywords: re-exploration; bleeding; tamponade; cardiac surgery